Mechanizing People and Pedagogy: Establishing Social Presence in the Online Classroom - Cunningham, Jennifer M. (Online Learning, 2015)
This research addresses the affordances of using Voki avatars to create a sense of social presence in an asynchronous online writing classroom setting. Digital media afford online educators the opportunity to harness different technologies and new ways of being in a digital classroom that can enhance student engagement in ways similar to yet unlike face-to-face instruction, but this current research questions the effectiveness of these technologies. Original data was obtained from forty students in an online writing course who responded to open-ended questions about their perception of social presence. This study reiterates the importance of establishing social presence in an online course, but suggests students may find specific Web 2.0 technology less effective than other pedagogical methods.